RNA polymerases reshape chromatin architecture and couple transcription on individual fibers. - Tullius, T.W.; Isaac, R.S.; Dubocanin, D.; Ranchalis, J.; Churchman, L.S.; Stergachis, A.B. (Molecular Cell, 2024)
RNA polymerases must initiate and pause within a complex chromatin environment, surrounded by nucleosomes and other transcriptional machinery. This environment creates a spatial arrangement along individual chromatin fibers ripe for both competition and coordination, yet these relationships remain largely unknown owing to the inherent limitations of traditional structural and sequencing methodologies. To address this, we employed long-read chromatin fiber sequencing (Fiber-seq) in Drosophila to visualize RNA polymerase (Pol) within its native chromatin context with single-molecule precision along up to 30 kb fibers. We demonstrate that Fiber-seq enables the identification of individual Pol II, nucleosome, and transcription factor footprints, revealing Pol II pausing-driven destabilization of downstream nucleosomes. Furthermore, we demonstrate pervasive direct distance-dependent transcriptional coupling between nearby Pol II genes, Pol III genes, and transcribed enhancers, modulated by local chromatin architecture. Overall, transcription initiation reshapes surrounding nucleosome architecture and couples nearby transcriptional machinery along individual chromatin fibers.